Nuclear tsunami the Japanese government and America's role in the Fukushima disaster - Krooth, Richard; Edelson, Morris; Fukurai, Hiroshi (Lexington Books, 2015)
This book shows how the bankruptcy of the central state of Japan has led to increased burdens on the population in the post-nuclear tsunami era, and the ensuing dangerous ionization of the population now reaching into the future.